RELATIONSHIP OF MARKETING TACTICS ON CONSUMER TRUST AND CONSUMER LOYALTY : THE CASE OF MEGA SANEL LESTARI PEKANBARU - Evelyn Wijaya; Suyono Suyono; Pamuji Hari Santoso (Journal of Applied Business and Technology, 2020)
Maintaining consumer loyalty is the main goal of relationship marketing. This is a way to build a long-term and mutually beneficial relationship between business owners and consumers. This study aimed to analyze the effect of relational marketing on consumer trust and consumer loyalty at Mega Sanel Lestari, Pekanbaru. The population in this study was consumers who made at least a purchase transaction at Mega Sanel Lestari, Pekanbaru with a total sample of 100 respondents. The study used SmartPLS 3 program. The results of the study indicate that relationship marketing and consumer trust have a significant positive effect on consumer loyalty and consumer trust. Consumer trust becomes the dominant variable in building and maintaining Consumer loyalty at Mega Sanel Lestari, Pekanbaru.